Comparison of water, helium, and carbon dioxide as coolants for next generation power plants using TRACE. (April 2019) - Garrett, Grant; Watson, Justin
Highlights: Added additional text to the introduction section to address the EOS and TRACE validation. Changed all figure formats to PDF to improve resolution. The number of significant figures in the tables is now consistent. References were fixed. Abstract: The purpose of this study is to compare the use of water, helium, and carbon dioxide as coolants for Generation IV and fusion power plants. In this study, the United States Nuclear Regulatory Commission's (NRC's) thermal hydraulics and neutronics coupled code TRAC/Relap Advanced Computational Engine (TRACE) was used to build and simulate a 600 MW th fusion Field Reversed Configuration (FRC) system that was cooled by either water, helium, or carbon dioxide. The results from the simulations, along with certain design criteria, were used to determine that water was the best coolant for the system of this study. For the operating conditions used in this research, water was able to keep the temperature of certain materials below their maximum temperatures much easier than the helium and carbon dioxide cooled systems. Specifically, beryllium was used as a material in the system and was determined to have a maximum temperature of 800 °C for its applications in this study (Mitteau et al., 2017). Additionally, this temperature limit restricts the efficiency and capabilities of the helium and carbon dioxide cooled systems. There is also uncertainty associated with the turbine efficiencies used in this study. This introduces uncertainty into the overall efficiency of the system for each coolant. So, the overall efficiency is not as important of a parameter in determining the best coolant for the system in this study as other parameters.